Women's Representation in the 2019 Legislative Election In Yogyakarta Special Region (DIY) - Dian Eka Rahmawati; Afiyatika Mufidati (PERSPEKTIF, 2021)
Legislative elections are a democratic instrument for selecting candidates who are expected to be able to channel people's aspirations in policy making. The presence of female candidates is expected to be able to influence the policy-making process related to women's needs and interests. In the 2019 legislative elections in the Special Region of Yogyakarta (DIY) there was an increase in the number of women at the candidacy stage and the number of elected candidates compared to the 2014 legislative elections. This study aims to analyze the factors that influence the electability of female candidates in the 2019 legislative elections in DIY. The results of the study found that there were differences in motivation between elected and unelected candidates. Strong motivation provides encouragement for female candidates to try their best to campaign for themselves with various strategies. Motivation as the main factor is supported by factors of network breadth, social and political experience, support and family background, and popularity.